2004
DOI: 10.1002/art.20569
|View full text |Cite
|
Sign up to set email alerts
|

A six‐month followup of a randomized trial comparing the efficacy of a lateral‐wedge insole with subtalar strapping and an in‐shoe lateral‐wedge insole in patients with varus deformity osteoarthritis of the knee

Abstract: Objective. To assess the effect of a lateral-wedge insole with elastic strapping of the subtalar joint on the femorotibial angle in patients with varus deformity of the knee.Methods. The efficacy of a wedged insole with subtalar straps and that of a traditional wedged insole shoe insert were compared. Sixty-six female outpatients with knee osteoarthritis (OA) were randomized (according to birth date) to be treated with either the strapped or the traditional inserted insole. Standing radiographs with unilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 20 publications
1
59
0
3
Order By: Relevance
“…The variable stiffness shoe results are in contrast to studies with laterally wedged insoles that in both healthy and subjects with OA have had mixed results (Baker et al, 2007;Bennell et al, 2011;Fang et al, 2006;Kakihana et al, 2007;Kutzner et al, 2011;Toda and Tsukimura, 2004). The mechanism by which the external adduction moment is reduced in the VS shoe is not clear.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…The variable stiffness shoe results are in contrast to studies with laterally wedged insoles that in both healthy and subjects with OA have had mixed results (Baker et al, 2007;Bennell et al, 2011;Fang et al, 2006;Kakihana et al, 2007;Kutzner et al, 2011;Toda and Tsukimura, 2004). The mechanism by which the external adduction moment is reduced in the VS shoe is not clear.…”
Section: Introductionmentioning
confidence: 57%
“…A comparison of the dynamic changes associated with the variable stiffness shoe to kinematic changes in fixed interventions such as lateral wedge shoes might help to explain the difference in the clinical outcome (Erhart et al, 2010) with this shoe relative to the inconsistent results seen with wedged interventions (Kakihana et al, 2007;Toda and Tsukimura, 2004). The primary difference between response to lateral wedge interventions and the variable stiffness shoe is the direction of shift in the COP in combination with the change in the m-l GRF (Fantini Pagani et al, 2011;Kakihana et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Toda and Tsukimura observed clinical and structural improvements at 6-month assessment in subjects who wore a subtalarstrapped lateral-wedge insole [12]. At the 6-month assessment, the subtalar-strapped lateral-wedge insole group demonstrated significantly decreased femorotibial angles, improved VAS scores, and improved Lequesne index scores compared with their baseline assessments, while those who wore the traditional shoe-insert wedge insole did not demonstrate changes [12]. At the 2-year assessment, the significantly decreased femorotibial angles and improved Lequesne index scores remained for those wearing the subtalar-strapped lateral-wedge insole [30].…”
Section: Discussionmentioning
confidence: 99%
“…At the 2-year assessment, the significantly decreased femorotibial angles and improved Lequesne index scores remained for those wearing the subtalar-strapped lateral-wedge insole [30]. Toda and Tsukimura suggested that the movement of the talus by the insole may interfere with calcaneal valgus correction and subsequently prevent femorotibial correction [12]. With the subtalar-strapped lateral-wedge insole, decreased femorotibial angles may restrict the progression of degenerative articular cartilage lesions of knee OA [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation